2022
DOI: 10.1155/2022/7752277
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced miR-210 Promotes Endothelial Cell Permeability and Angiogenesis via Exosomes in Pancreatic Ductal Adenocarcinoma

Abstract: Background. Exosomes have been proven to play important diagnostic, regulatory, or communication roles in tumorigenesis, tumor progression, or metastasis; in recent studies, lots of molecules, including miRNAs, were found to be aberrantly expressed in tumor exosomes and were correlated with tumor development. However, studies about the expression, relationship, or control mechanisms of miRNAs in exosomes in pancreatic ductal adenocarcinoma (PDAC) are scarce and urgently needed. The aim of this article was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Previous studies have reported that EFNA3 is targeted by miR-210 in multiple cell types [ 31 , 32 ]. However, the question of whether miR-210 could regulate EFNA3 in cardiomyocyte proliferation and/or apoptosis remained unanswered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that EFNA3 is targeted by miR-210 in multiple cell types [ 31 , 32 ]. However, the question of whether miR-210 could regulate EFNA3 in cardiomyocyte proliferation and/or apoptosis remained unanswered.…”
Section: Resultsmentioning
confidence: 99%
“…However, its role in the myocardium has been relatively underexplored. In addition, we evaluated EFNA3, a previously identified target of miR-210 [ 31 , 32 ], in the myocardium and in the I/R injury model after swimming regimen. Increasing evidence has indicated that EFNA3 participates to regulate apoptosis in different cell types such as nucleus pulposus cells, vascular endothelial cells, Müller cells, and sensory axon [ 59 – 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings imply that miR-210's promotion of proliferation and invasion, mediated through EFNA3, holds significance in MPNST tumourigenesis and progression [72]. Another study further elucidated the mechanism in PC, which indicates that miR-210 expression exhibits significant upregulation in both PDAC exosomes and malignant cells [73]. Elevated levels of miR-210 play a pivotal role in enhancing tumour angiogenesis, cell invasion, and proliferation in PDAC cells.…”
Section: Molecular Targets and Hallmarks Of Mir-210 Upregulation In P...mentioning
confidence: 86%
“…This participation facilitates tumor angiogenesis and enhances cellular permeability. In vivo studies have corroborated that exosomal miR-210 plays a significant role in driving the progression of pancreatic ductal adenocarcinoma [81,82]. Yu et al analyzed plasma levels of miR-196a and miR-210 with RT-qPCR in a cohort of 31 PDAC patients.…”
Section: Discussionmentioning
confidence: 99%